Aplikasi Metode Perhitungan Hydraulic Flow Unit (HFU) dalam Penentuan Persebaran Permeabilitas pada Model Reservoir Statis - Joko Pamungkas; Bambang Bintarto; Farah S Normaysti (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
AbstractPermeability in petrophysical analysis is one of the physical properties of rocks that determination productivity, reservoir in place, and fluid distribution in the reservoir. In this study, calculation for permeability distribution using the equation of crossplot between porosity and permeability from routine coredidn’t representative for S Field. Hydraulic Flow Unit (HFU) methodused to gave more representative distribution of permeability in static model.The method of calculated HFU on the S Field is divided into several methods such as : calculated HFU of routine core data (HFU Core), calculated HFU of routine core data and added with permeability and porosity from well test (HFU Core + Perm. Well test), calculatedHFU of routine core data and combined with oil rate from well test (HFU Core + Qo test), and calculatedHFU of routine core data and combined with cumulative oil production from each well (HFU Core + Np). Permeability distribution from HFU Method gave higher values of permeability for S Field than from single transformation (crossplot). The effect of calculated permeability distribution in static reservoir model with HFU method can be seen from oil in place. HFU Core + Np have better permeability distribution than other calculations. It can be seen from a comparison of oil in place (reserves of oil in the reservoir) between the calculation HFU Core + Np with single transformation (crossplot). Oil in place in the static model from the calculation with HFU Core + Npis 58.57 MMSTB while the oil in place with crossplotpermeability and porosity of routine core data is 46.88 MMSTB.